Medium-term energy hub management subject to electricity price and wind uncertainty - Najafi, Arsalan; Falaghi, Hamid; Contreras, Javier; Ramezani, Maryam (Applied energy, 2016)
•A new model for medium-term energy hub management is proposed.•Risk aversion is considered in medium-term energy hub management.•Stochastic programing is used to solve the medium-term energy hub management problem.•Electricity price and wind uncertainty are considered. Energy hubs play an important role in implementing multi-carrier energy systems. More studies are required in both their modeling and operating aspects. In this regard, this paper attempts to develop medium-term management of an energy hub in restructured power systems. A model is presented to manage an energy hub which has electrical energy and natural gas as inputs and electrical and heat energy as outputs. Electricity is procured in various ways, either purchasing it from a pool-based market and bilateral contracts, or producing it from a Combined Heat and Power (CHP) unit, a diesel generator unit and Wind Turbine Generators (WTGs). Pool prices and wind turbine production are subject to uncertainty, which makes energy management a complex puzzle. Heat demand is also procured by a furnace and a CHP unit. Energy hub managers should make decisions whether to purchase electricity from the electricity market and gas from the gas network or to produce electricity using a set of generators to meet the electrical and heat demands in the presence of uncertainties. The energy management objective is to minimize the total cost subject to several technical constraints using stochastic programming. Conditional Value at Risk (CVaR), a well-known risk measure, is used to reduce the unfavorable risk of costs. In doing so, the proposed model is illustrated using a sample test case with actual prices, load and wind speed data. The results show that the minimum cost is obtained by the best decisions involving the electricity market and purchasing natural gas for gas facilities. Considering risk also increases the total expected cost and decreases the CVaR.